The Effect of Principal Managerial and Professionalism of Teachers on the Implementation of School-Based Management - Slamet Riyadi; Ansori Ansori; Akhmad Ramli; Ratna Ayu Pawestri Kusuma Dewi; Hendrajaya Hendrajaya (Departement of Mathematics Education, 2023)
The goal of this study was to determine and evaluate the impact of teachers' professionalism and school leaders' managerial skills on the implementation of school-based management. Based on these goals, this study employs quantitative research techniques using a descriptive-inferential strategy. While primary data was gathered using a questionnaire instrument, secondary data were collected through observation, interviews, and documentation studies. Following that, the data was prepared and subjected to path analysis with a mixed multiple regression model. The research population consists of junior high school principals and instructors. The sampling strategy samples the entire population using the Slovin formula, which, rounded up, will result in a total of 150 samples. Following an analysis of the study's findings, it was discovered that managerial competence of school principals has a significant direct effect on teacher professionalism by 81.6%, a direct effect on school-based management by 77.4%, a direct effect on school-based management by 75.4%, and a combined significant direct effect on both teacher professionalism and managerial competence of school principals by 75.4%. Thus, the professionalism of teachers through the managerial skill of school principals has a 60.7% impact on management at the school.